2015
DOI: 10.1007/s10646-015-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficacy and toxic effect of emergency water disinfection process based on advanced oxidation technology

Abstract: An innovative and removable water treatment system consisted of strong electric field discharge and hydrodynamic cavitation based on advanced oxidation technologies was developed for reactive free radicals producing and waterborne pathogens eliminating in the present study. The biological efficacy and toxic effects of this advanced oxidation system were evaluated during water disinfection treatments. Bench tests were carried out with synthetic microbial-contaminated water, as well as source water in rainy seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The measurement of each chroma value was performed using a chroma instrument (CN60M/SD9011, Qiangdao Westmid Technology Co. Ltd., Qingdao, China) subsequent to centrifugation of each solution at 10,200× g for 10 min. Before measurements, the instrument was calibrated with platinum-cobaltic standard solutions at chroma values of 0, 50, 100, 250, and 500 [53]. The chroma value of 1 was defined as the color produced when there were 2 mg of hexaaquacobalt (IV) chloride hexahydrate and 1 mg of platinum (in the form of hexachloroplatinic (IV) acid) in each solution.…”
Section: Determination Of Removal Ratio Of Rbb Kn-rmentioning
confidence: 99%
“…The measurement of each chroma value was performed using a chroma instrument (CN60M/SD9011, Qiangdao Westmid Technology Co. Ltd., Qingdao, China) subsequent to centrifugation of each solution at 10,200× g for 10 min. Before measurements, the instrument was calibrated with platinum-cobaltic standard solutions at chroma values of 0, 50, 100, 250, and 500 [53]. The chroma value of 1 was defined as the color produced when there were 2 mg of hexaaquacobalt (IV) chloride hexahydrate and 1 mg of platinum (in the form of hexachloroplatinic (IV) acid) in each solution.…”
Section: Determination Of Removal Ratio Of Rbb Kn-rmentioning
confidence: 99%
“…These results indicate that rapid treatment of E. coli O157:H7 infection could serve to limit host metabolic impact and reduce overall host cell death. As for drinking water production, Tian et al (2015) reported an innovative and removable water treatment system for reducing waterborne pathogens, which consists of strong electric field discharge and hydrodynamic cavitation based on advanced oxidation technologies (AOT). The biological efficacy and toxicity effects of this AOT based system were evaluated during water disinfection treatments.…”
Section: Toxic Effect During Disinfection Processmentioning
confidence: 99%
“…In the field of environmental protection, DBD is used to obtain atmospheric non-equilibrium oxygen plasma to generate ozone based reactive oxygen species and combined with a certain treatment process, can decompose and kill pollutants and microorganisms. It mainly includes ship ballast water treatment [6], drinking water treatment [7,8], wastewater treatment [9], flue gas desulfurization and denitrification [10], etc.…”
Section: Introductionmentioning
confidence: 99%